Luxury Fashion and Sustainability: Digital Narratives, Greenwashing, and Consumer Engagement - Melanthiou, Yioula; Voutsa, Maria C. (My University, 2025)
Involvement of sustainability in marketing strategies has been significantly increased for luxury brands, often being criticized for practising greenwashing—an act of using unclear claims, selective transparency, and superficial efforts as a projection of environmental responsibility without being actionably sustainable. Claims of being “sustainable,” “green” and “eco,” or their products being “eco- friendly” and “eco-conscious,” could contribute to consumer scepticism especially in the absence of any third-party verification or concrete evidence of such claims. This chapter examines luxury fashion brands’ use of social media to advertise sustainability efforts and whether such advertisement claims translate into consumer engagement or rather enhance scepticism about greenwashing practices. This study investigates Instagram campaigns from the top luxury fashion brands and transits to a synoptic categorization of sustainability narratives under the United Nations Sustainable Development Goals (SDGs) for empirical insights into their effectiveness, credibility, and impact in communicating sustainability. The findings reveal gaps that exist between consumer expectations and the resultant engagement, how verification and transparency affect trust, and broader implications for sustainability communication in the luxury domain.
Keywords: sustainability; greenwashing; social media; engagement; Sustainable Development Goals (SDGs); transparency; trust; effectiveness; narratives; Earth Day; Blackout Tuesday